Major Outer Membrane Protein from Legionella pneumophila Inhibits Phagocytosis but Enhances Chemotaxis of RAW 264.7 Macrophages by Regulating the FOXO1/Coronin-1 Axis. (13th November 2021) - Yang, Zehui; Chen, Yingying; Zhang, Qiang; Chen, Xiaodong; Deng, Ze
Abstract : Legionella pneumophila is an intracellular pathogen that can cause Legionnaire's disease by invading alveolar epithelial cells and macrophages. The major outer membrane protein (MOMP) plays an important role in the interaction between bacteria and host cells. However, the role of MOMP in the process of L. pneumophila invasion of macrophages and its working mechanism remain unknown. We aimed to explore the effects of MOMP on phagocytosis and chemotaxis of RAW 264.7 macrophages. The chemotactic activity, toxicity, and phagocytosis of RAW 264.7 cocultured with different concentrations of MOMP were determined by Transwell, CCK-8, and neutral red uptake assays, respectively. Target genes were detected by double-luciferase and pull down assays. qRT-PCR and Western blot were performed to analyze the expression of several important proteins involved in the immune response pathway, including coronin-1, interleukins (IL-10), forkhead transcription factor 1 (FOXO1), nucleotide-binding oligomerization domain protein (NOD) 1, NOD2, and receptor-interacting protein (RIP) 2. After coculturing with MOMP, cytological observation indicated a decrease of phagocytosis and a marked increase of chemotaxis in RAW 264.7 macrophages. The phagocytosis degree of RAW 264.7 macrophage varied with the concentration gradient of MOMP in a time-dependent manner. MOMP could increase the expression levels of MCP-1, IL-10, NOD2, and RIP2 and decrease the expression levels of FOXO1 and coronin-1 in cell culture supernatants. In addition, we found that FOXO1 could promote its transcription by binding to the promoter of coronin-1. The results of the present study suggested that MOMP could inhibit phagocytosis and facilitate chemotaxis of RAW 264.7 macrophage, which might be associated with the FOXO1/coronin-1 axis.